2019
DOI: 10.1038/s42003-019-0558-4
|View full text |Cite
|
Sign up to set email alerts
|

Social and non-social autism symptoms and trait domains are genetically dissociable

Abstract: The core diagnostic criteria for autism comprise two symptom domains – social and communication difficulties, and unusually repetitive and restricted behaviour, interests and activities. There is some evidence to suggest that these two domains are dissociable, though this hypothesis has not yet been tested using molecular genetics. We test this using a genome-wide association study ( N = 51,564) of a non-social trait related to autism, systemising, defined as the drive to analyse and bui… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
80
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 125 publications
9
80
0
Order By: Relevance
“…A novel aspect of the current study is that we demonstrated statistically significant positive intra-couple correlations (and increased within-couple similarity) for self-reported systemizing (SQ-R scores) as well as for a behavioural/cognitive skill that likely underpins systemizing ability (speed on the EFT). This is particularly important considering that systemizing shares a genetic architecture with autism (Warrier et al, 2019), and, of course, because it is the trait upon which assortative mating in relation to autism was initially hypothesised to act (Baron- Cohen, 2006aCohen, , 2006bCohen, , 2007. These findings may therefore be informative regarding why autism is associated with interest and aptitude for STEM (Baron-Cohen et al, 1997, 2007Baron-Cohen, Wheelwright, Skinner, et al, 2001;Ruzich et al, 2015;Wei et al, 2013), and why children in geographical regions enriched with STEM industry are at elevated likelihood of developing the condition (Roelfsema et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A novel aspect of the current study is that we demonstrated statistically significant positive intra-couple correlations (and increased within-couple similarity) for self-reported systemizing (SQ-R scores) as well as for a behavioural/cognitive skill that likely underpins systemizing ability (speed on the EFT). This is particularly important considering that systemizing shares a genetic architecture with autism (Warrier et al, 2019), and, of course, because it is the trait upon which assortative mating in relation to autism was initially hypothesised to act (Baron- Cohen, 2006aCohen, , 2006bCohen, , 2007. These findings may therefore be informative regarding why autism is associated with interest and aptitude for STEM (Baron-Cohen et al, 1997, 2007Baron-Cohen, Wheelwright, Skinner, et al, 2001;Ruzich et al, 2015;Wei et al, 2013), and why children in geographical regions enriched with STEM industry are at elevated likelihood of developing the condition (Roelfsema et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we examined how autism SC-RRB balance subtypes are similar or different at the level of macroscale neural circuitry measured with rsfMRI. Prior work has suggested that the core dyad of SC and RRB is fractionable at behavior and neural levels and is underpinned by different genetic mechanisms [4][5][6][7][8][9][10][11][12][13][14] . However, it is unclear whether the road from genome to phenome (e.g., Figure 1) is one that converges on a common pathway or is one of multiple pathways 15 .…”
Section: Discussionmentioning
confidence: 99%
“…An example of this multi-scale heterogeneity can be seen at the level of the phenotypic symptom dyad of SC and RRB domains. Prior work has suggested that SC and RRB domains are fractionable at behavioral 4 and neural levels [5][6][7] and are underpinned by different genetic mechanisms [8][9][10][11] . The multi-scale fractionation of these domains provides a strong starting point for understanding how multi-scale heterogeneity manifests in autism from genome to phenome.…”
mentioning
confidence: 99%
“…As a starting point, there are several survey instruments, based on the DSM or ICD, that have been developed for cross‐national research (e.g., WMH‐CIDI; Kessler & Üstün, ). Keep in mind that symptom domains might be genetically and phenotypically dissociable (Warrier et al, ). Do not shackle your research to DSM/ICD categories and its symptom‐based approach. The DSM/ICD symptom‐based categories were largely developed based on inpatient populations in urban psychiatric hospitals in 19th and 20th century Europe and the United States (Harrington, ; Shorter, ; Zachar & Kendler, ).…”
Section: Discussionmentioning
confidence: 99%